LEGAL POLITICS FORMATION OF LEGISLATION IN THE INDONESIA NATIONAL LEGAL SYSTEM - Fernando, Zico Junius (Jurnal Hukum Progresif, 2022)
Indonesia is a state of law (rechtstaat) where the main joint of the national legal system is legislation. The conception of a state of law desired by the founding fathers since the beginning of the struggle for independence contains the basic ideas in the preamble to the 1945 Constitution of the Republic of Indonesia. Legislation is an instrument needed in national legal efforts. Discussing statutory regulations in essence, cannot be separated from discussing statutory politics based on the principle that laws and or statutory regulations are part of a political product. The form of statutory regulations in government can differ from laws and regulations in other governments. This depends on the authority of each government. Fundamental questions are related to the legal politics of forming laws and regulations in the national legal system and formulating regulations in the future. The discussion results show that the development of law and the updating of materials to be by the needs and implementation of existing provisions, as well as the preparation of laws and regulations, has a dimension of benefit that is large enough to realize the ideals of the formation of law.